2015
DOI: 10.1002/2015gl065501
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a new geomagnetic jerk in 2014

Abstract: The production of quasi‐definitive data at Ebre observatory has enabled us to detect a new geomagnetic jerk in early 2014. This has been confirmed by analyzing data at several observatories in the European‐African and Western Pacific‐Australian sectors in the classical fashion of looking for the characteristic V shape of the geomagnetic secular variation trend. A global model produced with the latest available satellite and observatory data supports these findings, giving a global perspective on both the jerk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
61
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(76 citation statements)
references
References 20 publications
7
61
0
Order By: Relevance
“…Using quiet-time monthly mean geomagnetic X, Y and Z data from four observatories, we investigated the occurrence as well as the strength of the 2014 geomagnetic jerk in Southern Africa, first reported by Torta et al (2015). Evidence of the 2014 geomagnetic jerk could be found in all field components, but not at all observatories.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using quiet-time monthly mean geomagnetic X, Y and Z data from four observatories, we investigated the occurrence as well as the strength of the 2014 geomagnetic jerk in Southern Africa, first reported by Torta et al (2015). Evidence of the 2014 geomagnetic jerk could be found in all field components, but not at all observatories.…”
Section: Discussionmentioning
confidence: 99%
“…An interesting feature of the most recent events in 2007 (Olsen et al 2009;Chulliat et al 2010) and 2012(Chulliat and Maus 2014Finlay et al 2015) is that they appear to have their origin from a succession of core field acceleration pulses occurring predominantly in West Africa and the South Atlantic region. The 2014 jerk was first reported by Torta et al (2015) showing evidence of strong secular acceleration in the Africa-South Atlantic region extending into Europe. Subsequently, Brown et al (2016) confirmed the presence of widespread jerks across the globe between 2013 and early 2015, including areas such as Alaska using more recent geomagnetic field and SWARM satellite data.…”
Section: Introductionmentioning
confidence: 99%
“…Torta et al, 2015). We suggest that the geomagnetic jerk concept should be considered as a more general notion, namely the evolution of the secular variation as a result of superposition of two (or more) constituents describing effects of processes in the Earth's core at two (or more) time-scales.…”
Section: Conclusion 10mentioning
confidence: 99%
“…It is worth to note that in terms of analysis shown in Figs. 6 and 7, the very recent geomagnetic jerks occurred in 2011 and 2014, evidenced for 20 limited areas by Chulliat and Maus (2014) and Torta et al (2015) in Atlantic sector and Atlantic and European sectors, respectively, reveal a strong influence of the decadal constituent at those dates. A more detailed analysis of the 11-year constituent of the secular variation is beyond the scope of this paper.…”
Section: Observatory Datamentioning
confidence: 99%
See 1 more Smart Citation